2013
DOI: 10.1080/01635581.2013.834945
|View full text |Cite
|
Sign up to set email alerts
|

Red Meat-Derived Heterocyclic Amines Increase Risk of Colon Cancer: A Population-Based Case-Control Study

Abstract: Formation of mutagenic heterocyclic amines (HCAs) and polycyclic aromatic hydrocarbons (PAHs) is one pathway believed to drive the association of colon cancer with meat consumption. Limited data exist on the associations of individual HCAs and PAHs in red or white meat with colon cancer. Analyzing data from a validated meat preparation questionnaire completed by 1,062 incident colon cancer cases and 1,645 population controls from an ongoing case-control study, risks of colon cancer were estimated using uncondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 32 publications
5
40
1
Order By: Relevance
“…2009a) which play an important role in the etiology of human cancer (Sugimura et al 2004;Skog and Solyakov 2002;Khan et al 2013;Khan el al. 2009a;Sugimura 2000;Alaejos et al 2008;Helmus et al 2013). In the framework of the Maillard reaction, amino acids, sugars and creatine are the main food constituents involved in the formation of such types of cooking toxicants (Murkovic 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2009a) which play an important role in the etiology of human cancer (Sugimura et al 2004;Skog and Solyakov 2002;Khan et al 2013;Khan el al. 2009a;Sugimura 2000;Alaejos et al 2008;Helmus et al 2013). In the framework of the Maillard reaction, amino acids, sugars and creatine are the main food constituents involved in the formation of such types of cooking toxicants (Murkovic 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The observed links among white and red meat consumption, the way of cooking the meat and DNA methylation profiles (Figures 5 & 6) is less clear. There is consensus indicating that high consumption of red and processed meat is a well known CRC risk factor, partially due to their mutagenic potential [49]. Therefore, the link among high meat consumption and the central cluster characterized by hypermethylation of the studied genes, could be an indirect association reflecting the fact that high meat consumption is more likely to be linked to non-CIMP CRCs evolving through the accumulation of gene mutations, than to those characterized by hypermethylation of several genes.…”
Section: Discussionmentioning
confidence: 97%
“…One article was subsequently excluded because it did not met the inclusion criteria since estimated the exposure to HCAs (low, intermediate and high) on the base of red meat source and preparation but not give their concentrations. Therefore, at the end of the selection process, 39 studies which met the inclusion criteria were enclosed in the systematic review and meta-analysis (Figure 1), 17 on CRA [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], 20 on CRC [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66], and 2 studies reported data on both CRA and CRC [67,68]. …”
Section: Resultsmentioning
confidence: 99%
“…Case-control studies were published between 1997 and 2015, 16 were population-based [48-57,62-65,67,68], 2 were hospital-based [47,58] and one was cohort-based [57]. Eighteen studies were conducted in the United States [49][50][51][52][53][54][55][56][57][59][60][61][62][63][64][66][67][68] and one each in Uruguay [47], Europe [48], Japan [58] and Canada [65]. Cohort studies were published between 2010 and 2016, all of them were conducted in the United States [60,61,66].…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%